The prevalence of mental health morbidity and its associated factors among women attending a prenatal clinic in Tanzania - Mahenge, Bathsheba; Stöckl, Heidi; Likindikoki, Samuel; Kaaya, Sylvia; Mbwambo, Jessie (International journal of gynecology & obstetrics, 2015)
Objective To establish the prevalence of symptoms of anxiety, depression, and post-traumatic stress disorder (PTSD) among women attending prenatal care in Tanzania, and identify associated factors. Methods A cross-sectional study was conducted of one in five physically well women attending a prenatal-care clinic in Muhimbili National Hospital, Dar es Salaam, between December 2011 and April 2012. Trained research assistants carried out face-to-face interviews using a structured questionnaire. The Hopkins Symptoms Checklist and the PTSD Diagnostic Scale were used to establish levels of depression and anxiety symptoms. Results Among the 1180 women interviewed, 905 (76.7%) had symptoms of anxiety, 923 (78.2%) had symptoms of depression, and 58 (4.9%) had moderate/severe PTSD symptoms. After adjustment for women's sociodemographic characteristics, age of the woman and their partner, educational level of the woman and their partner, relationship duration, employment, and marital status were associated with symptoms of at least one of the three mental disorders (P < 0.05 for all). Conclusion Many pregnant women had symptoms of mental health disorders. Screening of mental health disorders during prenatal care and training of healthcare providers are needed.